2022
DOI: 10.21608/jacb.2022.163494.1033
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Plant Growth Promoting of Salt-tolerant Rhizobacteria Isolated from Egyptian Saline Soils

Abstract: Plant growth promoting rhizobacteria (PGPR) are alternative strategy for mitigating the negative impacts of salinity stress on plants. The aim of this study was to isolate native PGPR with high plant growth promoting traits from Egyptian soils which could be used as an environmentally eco-friendly technique for alleviating salinity stress. Twenty-five Azotobacter spp. were isolated from Most Probable tubes, then all isolates were tested to grow in different concentrations of NaCl for salt tolerance. The highes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
(28 reference statements)
0
0
0
Order By: Relevance
“…These results agreed with the authors of [26,27], who stated that the Azotobacter isolate was found to be Na + -dependent, N 2 -fixing, and plant growth promoter strains. On the other hand, [28] found that some of the isolated bacteria showed remarkable plant growth-promoting traits, including high salt tolerance, N 2 fixation, P solubilization, and IAA production.…”
Section: Discussionmentioning
confidence: 99%
“…These results agreed with the authors of [26,27], who stated that the Azotobacter isolate was found to be Na + -dependent, N 2 -fixing, and plant growth promoter strains. On the other hand, [28] found that some of the isolated bacteria showed remarkable plant growth-promoting traits, including high salt tolerance, N 2 fixation, P solubilization, and IAA production.…”
Section: Discussionmentioning
confidence: 99%